Marginality as Lens: Abū Ḥāmid al-Qudsī’s Writings and Mamluk Urbanism - Lafi, Moaaz (AUC Knowledge Fountain, 2026)
This thesis takes the life and works of Abū Ḥāmid al-Qudsī (also known as al-Maqdisī), a Shāfiʿī jurist and Cairene historian who died in the late ninth/fifteenth century, as a point of entry into a central question: how was knowledge about the city produced in Mamluk Cairo? Addressing this question requires engagement with the multiple contexts, political, social, and religious, that shaped and conditioned the production of knowledge in that period. Moreover, a critical engagement with the author’s own biography, through a careful reading of biographical dictionaries and historical chronicles, is essential for uncovering further dimensions of how such knowledge was generated. The thesis does not limit itself to answering this question; rather, it extends the inquiry to examine how this knowledge has been re-represented in modern scholarship. It is striking that Abū Ḥāmid al-Qudsī, despite the many ambiguities and problems surrounding his historical profile, has been reconstituted in a markedly different form within contemporary Arabic writings, particularly within what is known as the “Fiqh al-ʿumrān” school, which has elevated his treatise al-Fawāʾid al-nafīsa to the status of a foundational text. This appropriation calls for careful scrutiny with regard to its accuracy and its limits. Accordingly, the study aims to make a dual contribution: first, to re-situate and correct the image of al-Qudsī within its proper historical context in order to better understand the conditions under which his knowledge was produced; and second, to deconstruct the representational and appropriative strategies embedded in the discourse of “Fiqh al-ʿumrān,” as well as to assess its impact on contemporary academic and cultural understandings.